Graphene composite building material and preparation method thereof

By mixing graphene nanosheets with concrete base and texturing a silk film on it, the problem of uneven dispersion of graphene powder in concrete is solved, the performance and hardness of composite building materials are improved, and the material usage and carbon emissions are reduced.

CN119707401AInactive Publication Date: 2025-03-28烟台理工学院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411918793.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When mixing graphene powder with concrete, it is difficult to disperse the graphene powder evenly, resulting in uneven concrete hardness.

Method used

By using graphene nanosheets and texturing a silk film thereon, it is mixed with the concrete base to form a graphene composite building material.

Benefits of technology

The uniform dispersion of graphene nanosheets in concrete is achieved, which improves the compressive strength, flexural strength and frost resistance of composite building materials, while reducing the use of concrete and carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207439700000031
    Figure BDA0005207439700000031
  • Figure BDA0005207439700000042
    Figure BDA0005207439700000042
  • Figure BDA0005207439700000051
    Figure BDA0005207439700000051
Patent Text Reader

Abstract

The invention relates to a graphene composite building material and a preparation method thereof, and belongs to the technical field of graphene building materials, the composite building material is prepared by mixing a concrete base material with graphene nanosheets; wherein the graphene nanosheet is prepared from the following raw materials in parts by weight: 20 to 35 parts of graphene nano powder, 8 to 16 parts of spinning solution, 6 to 12 parts of magnetic nano particle powder and 30 to 35 parts of 316 stainless steel powder. The graphene nanosheets are added into the composite building material, so that the compressive strength, the breaking strength and the splitting tensile strength after ultraviolet aging of the composite building material can be improved; the graphene nanosheets are arranged on the concrete base material, a layer of silk film is woven on the graphene nanosheets, the anti-freezing performance of the graphene nanosheets can be improved, the graphene nanosheets are mixed into the concrete base material, the usage amount of concrete can be reduced, carbon emission can be reduced, and the hardness of the composite building material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphene building materials, and specifically relates to a graphene composite building material and a preparation method thereof. Background Art

[0002] Graphene can be used in new building materials. Graphene is a material with excellent properties such as high strength, high toughness, low thermal conductivity, corrosion resistance, and anti-static properties. It is a new building material.

[0003] However, when graphene is generally used in building materials, graphene powder is usually mixed into concrete, which can increase the hardness of concrete and reduce the amount of concrete used. However, when graphene powder is mixed with concrete, it is difficult to evenly disperse the graphene powder into the concrete, which may cause the hardness of the concrete to be uneven. Summary of the invention

[0004] The purpose of the present invention is to provide a graphene composite building material and a preparation method thereof in order to solve the above problems.

[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0006] The invention provides a graphene composite building material, which is prepared by mixing a concrete base material with graphene nanosheets; wherein, by weight, the raw materials for preparing the graphene arc plate sheets include: 20-35 parts of graphene nanopowder, 8-16 parts of spinning solution, 6-12 parts of magnetic nanoparticle powder and 30-35 parts of 316 stainless steel powder.

[0007] As a further optimization scheme of the present invention, the preparation process of the spinning solution is: the polytetrafluoroethylene concentrated dispersion is heated to 60-80°C; carbon nanotubes, plant powder and phthalic anhydride are added to the polytetrafluoroethylene concentrated dispersion and stirred, and the spinning solution is obtained after sufficient mixing under a nitrogen environment.

[0008] As a further optimization scheme of the present invention, the raw materials for preparing the spinning solution include, by weight: 30-35 parts of polytetrafluoroethylene, 2-6 parts of carbon nanotubes, 10-15 parts of plant micropowder and 2-5 parts of phthalic anhydride.

[0009] As a further optimization scheme of the present invention, the preparation process of the plant micropowder is as follows: (1) taking the stems and leaves of Cistanche deserticola, dehydrating them by freeze drying, grinding them to a particle size of 1-2nm after dehydration, and stopping grinding to obtain Cistanche deserticola stem and leaf powder; (2) taking the stems and leaves of Ivy League, dehydrating them by freeze drying, grinding them to a particle size of 1-2nm after dehydration, and stopping grinding to obtain Ivy Leagueicola stem and leaf powder; (3) taking Cinnamomum camphora leaves, drying them indoors at 15-20°C, and then grinding them to a particle size of 1-3nm and stopping grinding to obtain Cinnamomum camphora leaf powder; mixing the Cinnamomum camphora stem and leaf powder, Ivy Leagueicola stem and leaf powder and Cinnamomum camphora leaf powder to obtain plant micropowder.

[0010] As a further optimization scheme of the present invention, the preparation process of the magnetic nanoparticle powder is: immersing the magnet powder in a silver ion solution for 28-32 hours, maintaining the temperature of the silver ion solution at 5-8°C, taking it out and drying it for 5-8 days to obtain the magnetic nanoparticle powder.

[0011] As a further optimization scheme of the present invention, the mass ratio of the Cistanche deserticola stem and leaf powder, Ivy sturgeon stem and leaf powder and Cinnamomum camphora leaf powder is 1:2:1.3.

[0012] As a further optimization scheme of the present invention, the mass ratio of the magnetic powder to the silver ion solution is 1:3.

[0013] As a further optimization scheme of the present invention, the raw materials for preparing the concrete base material include, by weight: 40-55 parts of river sand, 30-35 parts of Portland cement and 80-120 parts of tap water.

[0014] As a further optimization scheme of the present invention, the preparation process of the concrete base material is: injecting river sand, silicate cement and tap water into a mixer, stirring for 20-35 hours, and taking out to obtain the concrete base material.

[0015] The present invention also provides a method for preparing a graphene composite building material, comprising the following steps:

[0016] S1, stirring and mixing graphene nanopowder, magnetic nanoparticle powder and 316 stainless steel powder to obtain a prefabricated material;

[0017] S2, using a metal melting device to melt, shape, and cool the prefabricated material to obtain a prefabricated sheet;

[0018] S3, injecting the spinning solution into a high-voltage electrospinning device to spin a layer of silk film on the prefabricated sheet to obtain a graphene nanosheet;

[0019] S4, mixing the concrete base material with the graphene nanosheets to obtain a composite building material.

[0020] The beneficial effects of the present invention are as follows: adding graphene nanosheets to composite building materials makes it easy for the graphene nanosheets to be evenly mixed with concrete, facilitates the dispersion of graphene powder, and can increase the compressive strength, flexural strength and splitting tensile strength of the composite building materials after ultraviolet aging; and weaving a layer of silk film on the graphene nanosheets can increase the antifreeze performance of the graphene nanosheets, and mixing the graphene nanosheets into the concrete base material can reduce the use of concrete, reduce carbon emissions, and increase the hardness of the composite building materials. DETAILED DESCRIPTION

[0021] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0022] 1. Materials

[0023] Unless otherwise specified, the methods used in the present invention are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.

[0024] 2. Methods

[0025] 2.1 Effects of graphene nanosheets on the properties of composite building materials

[0026] (1) The preparation method of the composite building material is as follows:

[0027] The spinning solution preparation process is as follows: the polytetrafluoroethylene concentrated dispersion is heated to 70°C; carbon nanotubes, plant micropowder and phthalic anhydride are added to the polytetrafluoroethylene concentrated dispersion and stirred, and the spinning solution is obtained after being fully mixed under a nitrogen environment;

[0028] The preparation process of plant micro powder is as follows: (i) taking stems and leaves of Cnidium monnieri, dehydrating them by freeze drying, grinding them to a particle size of 2 nm after dehydration, and then stopping grinding to obtain stem and leaf powder of Cnidium monnieri; (ii) taking stems and leaves of Ivy bicolor, dehydrating them by freeze drying, grinding them to a particle size of 1 nm after dehydration, and then stopping grinding to obtain stem and leaf powder of Ivy bicolor; (iii) taking Cinnamomum camphora leaves, drying them indoors at 18°C, and then grinding them to a particle size of 1 nm and then stopping grinding to obtain Cinnamomum camphora leaf powder; mixing Cnidium monnieri stem and leaf powder, Ivy bicolor stem and leaf powder and Cinnamomum camphora leaf powder to obtain plant micro powder;

[0029] The preparation process of magnetic nanoparticle powder is as follows: immersing magnetic powder in a silver ion solution for 30 hours, maintaining the temperature of the silver ion solution at 6°C, taking out and drying for 7 days, and obtaining magnetic nanoparticle powder;

[0030] The preparation process of the concrete base material is as follows: inject river sand, silicate cement and tap water into a mixer, stir for 28 hours, and take out to obtain the concrete base material;

[0031] The graphene nanopowder, the magnetic nanoparticle powder and the 316 stainless steel powder are stirred and mixed to obtain a prefabricated material;

[0032] The prefabricated material is melted, formed and cooled by a metal melting device to obtain a prefabricated sheet;

[0033] The spinning solution is injected into a high-voltage electrospinning device to spin a layer of silk film on the prefabricated sheet to obtain a graphene nanosheet;

[0034] The concrete base is mixed with graphene nanosheets to obtain a composite building material.

[0035] The raw materials for preparing the spinning solution include: 32 parts of polytetrafluoroethylene, 4 parts of carbon nanotubes, 12 parts of plant micropowder and 3 parts of phthalic anhydride;

[0036] The mass ratio of Cistanche deserticola stem and leaf powder, Ivy stem and leaf powder and Cinnamomum camphora leaf powder is 1:2:1.3;

[0037] The mass ratio of magnet powder to silver ion solution is 1:3;

[0038] The raw materials for preparing the concrete base include: 50 parts of river sand, 33 parts of Portland cement and 100 parts of tap water.

[0039] The raw material composition of graphene nanosheets is shown in the following table:

[0040]

[0041]

[0042] Note: “-” means no addition

[0043] (2) The performance of the composite building material samples was tested using the following test methods:

[0044] The 3d and 28d compressive strength of cement mortar was used to characterize the strengthening and hardening effect. Portland cement (purchased from Wuxi Jianghuai Building Materials Technology Co., Ltd.) and river sand (ISO standard sand) were used for the test. The samples of composite building materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested for compressive strength and flexural strength according to "General Portland Cement" GB175-2020; UV aging test was performed using UV aging conditions: UV aging box (purchased from Suzhou Zhihe Environmental Testing Equipment Co., Ltd.), UV intensity of 210W / m2, aging temperature of 60°C, aging time of 10d, and the light aging of the composite building material sample test body prepared by the methods of Examples 1-3 and Comparative Examples 1-2 was observed.

[0045] The results are shown in the following table:

[0046]

[0047] The above data are the average values ​​of at least 10 measurements. It can be seen from the above table that the compressive strength and flexural strength performance of Example 2 are the best. Example 2 is compared with Comparative Example 1. The difference between Comparative Example 1 and Example 2 is that Comparative Example 1 does not use graphene nanopowder. It can be seen from the above table that Comparative Example 1 is not as good as Example 2 in compressive strength and flexural strength performance;

[0048] Example 2 is compared with Comparative Example 2. The difference between Comparative Example 2 and Example 2 is that Comparative Example 2 does not use spinning solution. It can be seen from the above table that at the 3rd day, the compressive strength and flexural strength performances of Comparative Example 2 and Example 2 are not much different, but at 28 days, the compressive strength and flexural strength performances of the lightweight foam concrete prepared by the method of Comparative Example 2 decrease.

[0049] 2.2 Effect of spinning solution on the properties of composite building materials

[0050] (1) Preparation method of composite building material The steps are as follows: 2.1-(1), wherein the spinning solution described in the following table is used instead of the spinning solution in Example 2.

[0051] The raw material composition of the spinning solution is shown in the following table:

[0052]

[0053] Note: “-” means no addition

[0054] (2) The performance of the composite building material samples was tested using the following test methods:

[0055] The composite building material samples were prepared using the methods of Example 2, Example 4 and Comparative Examples 3-4, and 40mm×40mm×160mm sample test bodies were formed in parallel according to the GB / T17671 method. After being cured for 5 years under standard conditions, frost resistance testing was carried out according to the T0565-2005 cement concrete frost resistance test method. Each freezing time was 30 minutes and the thawing time was 20 minutes. It was observed how many times the composite building material sample test bodies prepared by the methods of Example 2, Example 4 and Comparative Examples 3-4 showed cracking after being frozen.

[0056] The results are shown in the following table:

[0057]

[0058] It can be seen from the above table that the composite building materials with the addition of plant micropowder and phthalic anhydride have relatively good antifreeze properties and can be used in areas with lower temperatures.

[0059] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A graphene composite building material, characterized in that: The composite building material is prepared by mixing concrete base material with graphene nanosheets; Wherein, the raw materials for preparing the graphene nanosheets include, by weight: 20-35 parts of graphene nanopowder, 8-16 parts of spinning solution, 6-12 parts of magnetic nanoparticle powder and 30-35 parts of 316 stainless steel powder.

2. A graphene composite building material according to claim 1, characterized in that: The spinning solution preparation process is as follows: the polytetrafluoroethylene concentrated dispersion is heated to 60-80° C.; carbon nanotubes, plant micropowder and phthalic anhydride are added to the polytetrafluoroethylene concentrated dispersion and stirred; and the spinning solution is obtained after fully mixing under a nitrogen environment.

3. A graphene composite building material according to claim 2, characterized in that: The raw materials for preparing the spinning solution include, by weight: 30-35 parts of polytetrafluoroethylene, 2-6 parts of carbon nanotubes, 10-15 parts of plant micropowder and 2-5 parts of phthalic anhydride.

4. A graphene composite building material according to claim 3, characterized in that: The preparation process of the plant micropowder is as follows: (i) taking the stems and leaves of Cnidium monnieri, dehydrating them by freeze drying, grinding them to a particle size of 1-2 nm after dehydration, and then stopping grinding to obtain Cnidium monnieri stem and leaf powder; (ii) taking the stems and leaves of Ivy bicolor, dehydrating them by freeze drying, grinding them to a particle size of 1-2 nm after dehydration, and then stopping grinding to obtain Ivy bicolor stem and leaf powder; (iii) taking Cinnamomum camphora leaves, drying them indoors at 15-20° C., and then grinding them to a particle size of 1-3 nm and then stopping grinding to obtain Cinnamomum camphora leaf powder; and mixing the Cnidium monnieri stem and leaf powder, the Ivy bicolor stem and leaf powder and the Cinnamomum camphora leaf powder to obtain the plant micropowder.

5. A graphene composite building material according to claim 1, characterized in that: The preparation process of the magnetic nanoparticle powder is as follows: immersing the magnet powder in a silver ion solution for 28-32 hours, maintaining the temperature of the silver ion solution at 5-8° C., taking out and drying for 5-8 days, and obtaining the magnetic nanoparticle powder.

6. A graphene composite building material according to claim 4, characterized in that: The mass ratio of the Cistanche deserticola stem and leaf powder, the Ivy League stem and leaf powder and the Cinnamomum camphora leaf powder is 1:2:1.

3.

7. A graphene composite building material according to claim 5, characterized in that: The mass ratio of the magnetic powder to the silver ion solution is 1:

3.

8. The graphene composite building material according to claim 1, characterized in that: The raw materials for preparing the concrete base material include, by weight: 40-55 parts of river sand, 30-35 parts of Portland cement and 80-120 parts of tap water.

9. A graphene composite building material according to claim 8, characterized in that: The preparation process of the concrete base material is as follows: injecting river sand, silicate cement and tap water into a mixer, stirring for 20-35 hours, and taking out to obtain the concrete base material.

10. A method for preparing the graphene composite building material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, stirring and mixing graphene nanopowder, magnetic nanoparticle powder and 316 stainless steel powder to obtain a prefabricated material; S2, using a metal melting device to melt, shape, and cool the prefabricated material to obtain a prefabricated sheet; S3, injecting the spinning solution into a high-voltage electrospinning device to spin a layer of silk film on the prefabricated sheet to obtain a graphene nanosheet; S4, mixing the concrete base material with the graphene nanosheets to obtain a composite building material.